Innovation and Performance during the Financial Crisis (Global Journal of Management and Business Research, 2018)
This research is a contribution to establish an empirical background on the capacity for innovation in French firms listed on the SBF 120 covering the period before and after the financial crisis. The purpose of this research paper is to analyze the factors that influence the capacity for innovation and to prove the existence of a possible relationship between the innovation capacity and the performance. Firstly, the study reveals that research and development expenditure has a negative impact on the financial performance of SBF 120 firms during the period from 2004 to 2016. Secondly, this negative relationship between performance and innovation persists during the pre and post financial crisis period.
Keywords: innovation; performance; research and development; plurality functions of manager